Povidone Iodine (PVP-I) mouth gargle/nasal spray may be the simplest and cost effective therapeutic antidote for COVID-19 Frontier - Khalil, Ibrahim; Barma, Parometa (Archives of Community Medicine and Public Health, 2020)
Need an effective protocol for health workers against dangerous and unpredictable SARS CoV-2, a RNA lipid bi-layer enveloped beta-coronaviruses which contains Hemagglutinin Esterase (HE) protein binds with human gene through Angiotensin-Converting-Enzyme 2 (ACE2) and CD147 receptor. Povidone-iodine (PVP-I) has effective virucidal activity by those receptors inhibition and direct kill the virus by membrane disruption. PVP-I gargle, nasal spray and eye drop in case of accidental exposure is well tolerated easy use and has 2-3 hours contamination protection properties. So, uses gargle and nasal spray every 3 hours during shifting duty of health care provider which will cover the total protection and reduced social contamination.